Multiple aseptic abscesses and pulmonary involvement in a child with Behcet’s disease phenotype: a case report - Yucan Zheng; Guiping Kong; Hongmei Guo; Zhifeng Liu; Kunlong Yan (Frontiers in Immunology)
BackgroundBehcet’s disease (BD) is a lifelong multi-systemic vasculitis disorder that can affect almost any organ. The frequency of involvement of each organ varies depending on demographic and geographical factors. The commonly affected systems include mucosal, articular, ocular, vascular, neurological, and gastrointestinal. Common gastrointestinal manifestations include mucosal ulcers, hemorrhage, and perforation while other phenotypes are very rare.Case presentationWe describe the case of a 3-year-old boy suffering from BD phenotype with multiple aseptic abscesses (AAs) and interstitial lung disease. Over the past four years since onset, the boy has presented a series of symptoms, including fever, skin necrosis, multiple ulcers in the intestines, multiple aseptic abscesses in the spleen, interstitial lung disease and an isolated abscess in the gastric wall. Through a regimen involving steroids, mercaptopurine, thalidomide endoscopic drainage of the gastric wall abscess, the child’s condition has been effectively managed and improved.ConclusionTo our knowledge, this is the first reported case of BD phenotype with a gastric wall abscess treated with endoscopic drainage and steroids. Multiple AAs and interstitial lung disease may be the early signs of a BD phenotype in childhood which can respond effectively to glucocorticoids.